PENGARUH PENERAPAN METODE EKSPERIMEN DARI BAHAN ALAM TERHADAP PERKEMBANGAN KOGNITIF ANAK USIA 5-6 TAHUN - Devi, Sri; Syukri, M.; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to determine the effect of experimental of natural materials on cognitive children aged 5-6 years. Using quantitative methods form of real experiments, pretest-posttest group design. Samples is 30 people. Data collection observation and documentation. The technique analyzing data is descriptive analysis looking at the average and the t test present the results of t test. Based on the results of data analysis about effect the application of experimental methods of natural materials on cognitive development of children aged 5-6 years by comparing the experimental group and the control group. The results of the study show the value of tcount is 16,884. While the value of ttable with a significance level of 5% for one side and 0.651 (for two sides) with a degree of freedom 28 then obtained 2.048. Because tcount> ttable (16,884> 2,048), null hypothesis is rejected. There is an influence the applicatio experimental methods from natural materials on cognitive development children aged 5-6 years. Calculated using a coefficient of determination formula of 22.18% the effect of application of the experimental method of natural materials on cognitive development of children aged 5-6 years. The conclusion is the effect the experimental method of natural materials affects cognitive. Keywords: Children, Cognitive, Experimental